Evolutionary significance of seed structure in Alpinioideae (Zingiberaceae). (9th March 2015) - Benedict, John C.; Smith, Selena Y.; Collinson, Margaret E.; Leong‐Škorničková, Jana; Specht, Chelsea D.; Fife, Julie L.; Marone, Federica; Xiao, Xianghui; Parkinson, Dilworth Y.
<x xml:space="preserve">Abstract</x> Alpinioideae is the largest of the four subfamilies of Zingiberaceae and is widely distributed throughout the New and Old World tropics. Recent molecular studies have shown that, although Alpinioideae is a strongly supported monophyletic subfamily with two distinct tribes (Alpinieae and Riedelieae), large genera, such as Alpinia and Amomum, are polyphyletic and are in need of revision. Alpinia and Amomum have been shown to form seven and three distinct clades, respectively, but, for many of these clades, traditional vegetative and floral synapomorphies have not been found. A broad survey of seeds in Alpinioideae using light microscopy and synchrotron‐based X‐ray tomographic microscopy has shown that many clades have distinctive seed structures that serve as distinctive apomorphies. Tribes Riedelieae and Alpinieae can be distinguished on the basis of operculum structure, with the exception of three taxa analysed. The most significant seed characters were found to be various modifications of the micropylar and chalazal ends, the cell shape of the endotesta and exotesta, and the location of an endotestal gap. A chalazal chamber and hilar rim are reported for the first time in Zingiberaceae. In addition to characterizing clades of extant lineages, these data offer insights into the taxonomic placement of many fossil zingiberalean seeds that are critical to understanding the origin and evolution of Alpinioideae and Zingiberales as a whole. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 178, 441–466..